A 3D Porous Gelatin-Alginate-Based-IPN Acts as an Efficient Promoter of Chondrogenesis from Human Adipose-Derived Stem Cells - Sorina Dinescu; Bianca Galateanu; Eugen Radu; Anca Hermenean; Adriana Lungu; Izabela Cristina Stancu; Dana Jianu; Tudorita Tumbar; Marieta Costache (Stem Cells International)
Cartilage has limited regeneration potential. Thus, there is an imperative need to develop new strategies for cartilage tissue engineering (CTE) amenable for clinical use. Recent CTE approaches rely on optimal cell-scaffold interactions, which require a great deal of optimization. In this study we attempt to build a novel gelatin- (G-) alginate- (A-) polyacrylamide (PAA) 3D interpenetrating network (IPN) with superior performance in promoting chondrogenesis from human adipose-derived stem cells (hADSCs). We show that our G-A-PAA scaffold is capable of supporting hADSCs proliferation and survival, with no apparent cytotoxic effect. Moreover, we find that after exposure to prochondrogenic conditions a key transcription factor known to induce chondrogenesis, namely, Sox9, is highly expressed in our hADSCs/G-A-PAA bioconstruct, along with cartilage specific markers such as collagen type II, CEP68, and COMP extracellular matrix (ECM) components. These data suggest that our G-A-PAA structural properties and formulation might enable hADSCs conversion towards functional chondrocytes. We conclude that our novel G-A-PAA biomatrix is a good candidate for prospective in vivo CTE applications.